Formulation and Antioxidant Test of Baby Instant Porridge with Kepok Banana Flour and Tempe - Sukardi Sukardi; Selvy Triskiana Wista; Vritta Amroini Wahyudi (Food Technology and Halal Science Journal, 2021)
Commercial instant porridge generally chooses to use rice flour as a carbohydrate source, including instant porridge specifically for babies. The high current consumption of rice is encouraging various food diversification efforts to avoid dependence on one commodity. Kepok banana flour can be used as a substitute for carbohydrates in instant baby porridge, mainly from rice flour and tempe as a source of protein. Banana leaves and teak leaves were chosen as a wrapper for tempe to affect the chemical and organoleptic properties of instant baby porridge. The purpose of this study was to obtain instant baby porridge products which have nutritional value according to the SNI 01-71111.1-2005 standards regarding complementary foods. This study used a completely randomized design (CRD), consist of tempe packaging, namely banana leaves and teak leaves, which were carried out three times using the pairwise difference test (t-test) as a statistical test. Instant baby porridge with tempe treatment packed with banana leaves is an instant baby porridge that is closest to SNI 01-7111.1-2005 concerning complementary feeding with a moisture content value of 18.89%, ash content 2.71%, protein content 6.66%, fat content 16.96%, carbohydrate content 54.77%, 76.70% antioxidant activity, and the highest preference level with a value of 4.87